Strategi Peningkatan Keberlanjutan Daya Saing Teh Organik - Titah Haritul Ichwani; Arief Daryanto; Anas Miftah Fauzi (School of Business, Bogor Agricultural University (SB-IPB), 2019)
Tea industry is a promising industry, especially with its global awareness about organic tea. The purpose of this study is to identify the best alternative strategies for PT Harendong Green Farm to survive and sustainable. Technique of data collecting was conducted by interviewing the experts and distributing the questioners to five respondents, consisting of CEO, Plantation Head and Production Head of PT Harendong Green Farm, Head of Promotion Board of Indonesia, and Tea Master. The data analysis was carried out using Analytical Hierarchy Process (AHP) method to determine strategy in detail and priority development activity for the company. AHP results show that the procurement of premium tea products, competitive pricing, attractive packaging and cultural orientation through education and understanding to the community become an alternative offered. The recommended strategy is to establish a premium tea product from a competing company with a distinctive fragrance and flavor.Keywords: competitiveness, organic certificates, organic tea, premium tea, AHPAbstrak: Industri teh merupakan salah satu industri yang menjanjikan, terutama dengan kesadaran masyarakat global tentang teh organik. Tujuan Penelitian ini adalah untuk mengidentifikasikan alternatif strategi yang terbaik bagi perusahaan agar dapat bertahan serta berkelanjutaan. Teknik pengumpulan data menggunakan wawancara pakar dan pengisian kuesioner oleh lima responden yaitu CEO, Kepala Perkebunan dan Kepala Produksi PT Harendong Green Farm, Kepala Promosi Dewan Teh Indonesia dan Tea Master. Analisis data menggunakan metode Analytical Hierarchy Process (AHP) untuk menentukan strategi secara detail dan prioritas utama pengembangan kegiatan perusahaan. Hasil AHP menunjukkan bahwa pengadaan produk teh premium, harga yang kompetitif, kemasan yang menarik dan orientasi budaya melalui edukasi dan pemahaman kepada masyarakat menjadi alternatif yang ditawarkan. Strategi yang disarankan adalah dengan mengadakan produk teh premium yang berbeda dari perusahaan pesaing dengan menonjolkan aroma dan rasa yang khas.Kata kunci: daya saing, sertifikat organik, teh organik, teh premium, AHP